MUTATIONS IN THE LCAT GENE AND CLINICAL HETEROGENEITY: MAPPING GENOTYPE-PHENOTYPE CORRELATIONS (REMUNOM, 2026)
Lecithin-cholesterol acyltransferase (LCAT) deficiency is a rare autosomal recessive disorder characterized by significant genetic and phenotypic heterogeneity. More than 100 different mutations have been identified in the LCAT gene, resulting in two distinct clinical phenotypes: familial LCAT deficiency (FLD) and fisheye disease (FED). This study aimed to conduct an integrative literature review to identify and characterize mutations in the LCAT gene, emphasizing genotype-phenotype correlations and the mechanisms that determine clinical variability. An active search was conducted in electronic databases (PubMed, MedLine, SciELO, and LILACS) between January 2011 and December 2025, following PRISMA recommendations. Study selection was performed by two independent reviewers, analyzing titles, abstracts, and full texts, applying predefined inclusion and exclusion criteria. Nineteen studies describing specific mutations, clinical phenotypes, and biochemical data were included. The results demonstrate significant variation in the distribution of missense, nonsense, and frameshift mutations along the LCAT gene. Notable phenotypic heterogeneity was observed, with patients carrying identical genotypes presenting distinct clinical manifestations, including variations in renal involvement, ophthalmological manifestations, anemia, and lipid profile. A founder effect was identified in isolated populations, particularly in Brazilian families from Piauí. The genotype-phenotype correlation is not linear, suggesting an important role for genetic, environmental, and epigenetic modifying factors. These findings contribute to a better understanding of the molecular and clinical mechanisms of LCAT deficiency, fundamental for future diagnostic and therapeutic approaches in rare diseases.